Organ-preserving approach to the treatment of patients with uterine fibroids and congenital anomaly of the urinary system (a clinical case) - B.M. Sharafutdinov; M.I. Mazitova; S.A. Ryzhkin; I.V. Abdul'yanov; Ya.V. Prokop'ev (LCC «Medicine-Inform», 2022)
E.Yu. Antropova1, B.M. Sharafutdinov1,2, M.I. Mazitova1, S.A. Ryzhkin3-6, I.V. Abdul'yanov1,7, Ya.V. Prokop'ev1 1Kazan State Medical Academy - Branch of the Russian Medical Academy of Continuous Professional Education, Kazan, Russian Federation 2Medical Wing of the Kazan Federal University, Kazan, Russian Federation 3Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation 4Kazan State Medical University, Kazan, Russian Federation 5Federal Center of Toxicological, Radiation and Biological Safety, Kazan, Russian Federation 6Institute of Physics, Kazan Federal University, Kazan, Russian Federation 7Interregional Clinical and Diagnostic Center, Kazan, Russian Federation Congenital anomalies of the urogenital system constitute approximately 20 to 30% of all birth defects. Renal dystopia means a congenital abnormal location of one or both kidneys. The authors present a clinical case report, demonstrating the efficacy of uterine artery embolization as an alternative method of treatment for patients with uterine fibroids and renal dystopia. Uterine artery embolization is not only an organ-preserving treatment option for women who wish to retain the reproductive organ but also offers a clear visualization of the individual anatomical variations. Taking into consideration a strong patient's wish to preserve the uterus and her individual vascular anomalies (absence of the left uterine and renal arteries), uterine artery embolization was an alternative treatment option which enabled to preserve both the uterus and the left kidney. The scheduled examination findings demonstrated a 1.87-fold reduction of the uterine volume and a 12.8-fold reduction of the fibroid size from baseline, and color doppler ultrasonography revealed that the uterine fibroid was avascular. For patients with diagnosed congenital anomalies of the urogenital system, the authors recommend using computer tomography an d referrals to interdisciplinary specialists for choosing the appropriate uterine fibroid treatment options. Keywords: uterine fibroids, pelvic kidney dystopia, uterine artery embolization, organ-preserving treatment methods, congenital anomalies of the urogenital system, computer tomography. For citation: Antropova E.Yu., Sharafutdinov B.M., Mazitova M.I. et al. Organ-preserving approach to the treatment of patients with uterine fibroids and congenital anomaly of the urinary system (a clinical case). Russian Journal of Woman and Child Health. 2022;5(4):320-325 (in Russ.). DOI: 10.32364/2618-8430-2022-5-4-320-325.